About Culture, Cultural Anthropology, Anthropologies and Social Sciences. Answer to Nikola Balaš - Paleček, Martin (Teorie vědy / Theory of Science, 2019)
Discussion paper dedicated to the paper Nikola Balaš, „Kdo je tu v pasti?“ Teorie vědy / Theory of Science 41, no. 1 (2019): 133–49.